Mechanistic information on the reductive elimination from cationic trimethylplatinum(IV) complexes to form carbon-carbon bonds - Zahl, Achim; van Eldik, Rudi; Liehr, Günter; et al. (Inorganic Chemistry, 2005)
Cationic complexes of the type fac-[(L)PtMe (pyr-X)][OTf] (pyr-X = 4-substituted pyridines; L = diphosphine, viz., dppe = bis(diphenylphosphino)ethane and dppbz = o-bis(diphenylphosphino)benzene; OTf = trifluoromethane-sulfonate) undergo C-C reductive elimination reactions to form [LPtMe(pyr-X)] [OTf] and ethane. Detailed studies indicate that these reactions proceed by a two-step pathway, viz., initial reversible dissociation of the pyridine ligand from the cationic complex to generate a five-coordinate Pt intermediate, followed by irreversible concerted C-C bond formation. The reaction is inhibited by pyridine. The highly positive values for ΔS = +180 ± 30 J K mol , ΔH = 160 ± 10 kJ mol, and ΔV = +16 ± 1 cm mol can be accounted for in terms of significant bond cleavage and/or partial reduction from Pt to Pt in going from the ground to the transition state. These cationic complexes have provided the first opportunity to carry out detailed studies of C-C reductive elimination from cationic Pt complexes in a variety of solvents. The absence of a significant solvent effect for this reaction provides strong evidence that the C-C reductive coupling occurs from an unsaturated five-coordinate Pt intermediate rather than from a six-coordinate Pt solvento species. © 2005 American Chemical Society.